William C. Nell correspondence - Nell, William C. (William Cooper), 1816-1874.
ALS (1859 December 14; Boston, Mass.) from Nell to Mr. Drake concerning Drake's request for a book.
Historian, abolitionist, and postal clerk of Boston.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Abolitionists; Historians; Postal clerks